Formulasi dan Karakterisasi Nanokapsul Asiklovir Tersalut Kitosan-Alginat yang Dipaut Silang dengan Natrium Tripolifosfat - Isriany Ismail; Hasriani Hasriani; Surya Ningsi (Universitas Islam Negeri Alauddin Makassar, 2014)
Formulation and characterization of chitosan-alginate crosslinked with sodium tripolyphosphate as coating agents acyclovir nanocapsule purposed to determine how the comparison the coating of chitosan and sodium alginate crosslinked with sodium tripolyphosphate produce the best nanocapsule characteristics based on morphological observations and encapsulation efficiency. Nanocapsule formulation by the ionic gelation method by using chitosan concentrates variation on formula A, B, and C in succession 1.5%, 1.75%, and 2%, sodium alginate 0.5%, 0.625%, and 0.75% with stable concentration of sodium tripolyphosphate is 5%. Nanocapsule was measured using UV-Vis spectrophotometer at a wavelength of 297 nm with encapsulation efficiency obtained from the formula A, B and C, respectively for 58.5%; 87.25% and 55.25%. Observation of the shape and size of nanocapsule performed using SEM. Formula B with concentration of chitosan 1.75%, sodium alginate 0.625% and sodium tripolyphosphate 5% has the best characteristics with the encapsulation efficiency 87.25%, that the smallest particle size was 200 nm and the largest particle size was 4500 nm.